(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Creative thinking is a psychological process and a psychological activity, its essence the main qualities are quickness, flexibility, unique images, concepts and to reflect and change the surrounding world through the formation of mental actions is characteristic. Clarity - they simultaneously serve as a criterion for the process being studied. Also the communication and relationships between people in social life, educational process and production manifestation with the help of thinking, deepening of their thinking during the period of studying in the upper class stated about.